Hak Kepemilikan Kain Sisa Jahitan dalam Tinjauan Fikih Muamalah (Studi Kasus Malaabis Makassar) - Rosmita Rosmita; Nuraeni Novira; Yumita Yumita (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2023)
This research aims to find out and understand how the ownership rights of leftover stitched fabric are in the Muamalat jurisprudence review. The problems that the author raises in this research are: first, what is the practice of owning stitched leftover fabric in Malaabis Makassar? Second, what is the background behind tailors using stitched leftover cloth? Third, what are the ownership rights of the remaining Makassar Malaabis stitched fabric in the Muamalat jurisprudence review? The method used is a qualitative research method, using a type of field research carried out at Malaabis Makassar, with data collection through observation, interviews and documentation. The research approaches used are theoretical, normative juridical and phenomenological approaches. The results of research in the field show that Malaabis Makassar does not return leftover stitched fabric and does not offer leftover stitched fabric to customers. In muamalat fiqh, the remaining stitched fabric is the perfect property (al-milku al-tam) of the orderer. The phenomenon of tailors not returning leftover sewing fabric occurs because tailors feel that the customer no longer needs their remaining stitching fabric, the customer doesn't care about the ownership rights of the remaining stitched fabric and the tailor does not disclose the remaining stitched fabric. A tailor who uses fabric left over from a customer can be said to be permissible, when it is clear that the customer is satisfied with it or by looking at the habits of the people who no longer need fabric left over from sewing. This research has implications for society in general, both tailors who do not return leftover stitched fabric and buyers who do not care about their stitched leftover fabric.